2019
DOI: 10.1111/ina.12620
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ultrafine particles in children until 18 years of age: A systematic review

Abstract: Airborne ultrafine particles (UFP) have been related to adverse health effects, but exposure in vulnerable population groups such as children is still not well understood. We aim to review the scientific literature regarding personal exposure to UFP in different microenvironments in populations until 18 years of age. The bibliographical search was carried out in July 2019 using the online database PubMed and was completed with references in articles found in the search. We selected the studies that used contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
0
12
0
1
Order By: Relevance
“…13 studies focused on office buildings, 34,42‐44,46,67,69,71,72,74‐76,80 26 studies were related to schools, 25,27,29,35,38‐41,43,47‐49,51,52,54,56,58,60,61,64‐66,68,72,73,77 and 20 studies investigated residences 28,30‐33,36,37,45,50,53,55,57,59,62,63,70,72,77‐79 . Schools were the most studied microenvironments, probably because the intensive density of students is more likely to cause microorganisms, and health policies often target at schools 81 . More than half of these researches on schools were done on university campuses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 studies focused on office buildings, 34,42‐44,46,67,69,71,72,74‐76,80 26 studies were related to schools, 25,27,29,35,38‐41,43,47‐49,51,52,54,56,58,60,61,64‐66,68,72,73,77 and 20 studies investigated residences 28,30‐33,36,37,45,50,53,55,57,59,62,63,70,72,77‐79 . Schools were the most studied microenvironments, probably because the intensive density of students is more likely to cause microorganisms, and health policies often target at schools 81 . More than half of these researches on schools were done on university campuses.…”
Section: Resultsmentioning
confidence: 99%
“…28,[30][31][32][33]36,37,45,50,53,55,57,59,62,63,70,72,[77][78][79] Schools were the most studied microenvironments, probably because the intensive density of students is more likely to cause microorganisms, and health policies often target at schools. 81 More than half of these researches on schools were done on university campuses. Compared to fungi, researchers were more concerned with bacterial concentrations, with 48 studies reported bacterial concentration levels, 25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][53][54]…”
Section: Search Findingsmentioning
confidence: 99%
“…https://doi.org/10.1183/16000617.0116-2020 measurement sites to allow more powerful studies. Previous reviews have also reported the difficulty in combining information from multiple studies due to the wide differences in exposure assessment methods [29]. The comparison of results from different studies is even harder considering their use of various exposure periods, age groups and respiratory morbidity indexes.…”
Section: Figurementioning
confidence: 99%
“…Moreover, residential indoor air quality is seldom subject to official regulations. For a better understanding of indoor air quality, further studies on indoor particle exposure, in particular ultrafine particles, are needed 11–14 …”
Section: Introductionmentioning
confidence: 99%
“…For a better understanding of indoor air quality, further studies on indoor particle exposure, in particular ultrafine particles, are needed. [11][12][13][14] Aerosol particles in indoor air are usually a mixture of particles originating from indoor and outdoor various sources, where particle size distribution and chemical composition change over time. This change is dominated by several processes and factors such as the emission profile of indoor sources, the building shell penetration factor, the ventilation rate, and particle losses due to deposition on surfaces and coagulation.…”
mentioning
confidence: 99%